Obtaining composite materials based on polycarbonate - Nuritdinov, Abdullazizbek; Kamalov, Akmalxon; Abdulalimov, Obidjon; To`raxonov, Ravshanbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This work analyzed the effect on the mechanical and environmental properties of composites based on recycled compact discs (CDs) and digital optical discs (DVDs) based on plastic polycarbonate waste and on the basis of gypsum raw materials. Fifteen mixtures containing different weight percentages of plastic aggregate with two different granulometries were produced. In each case, the strength properties (flexural and compressive) and density of the new composites were tested. In addition, scanning electron microscopy (SEM) and X-ray computed tomography (XCT) were conducted to find out the internal structure and porosity of the new composites. The results show that in some cases it is possible to obtain lighter and more economical materials with better mechanical properties than the reference material (gypsum). A density reduction of 9.89% was achieved for mixtures with 60% plastic waste. These properties make composites suitable for use in industrial sectors from new products.